The Effect Of Risk Perception And Locus Of Control On Investment Decisions With Financial Literacy As A Moderating Variable - Permana, Salma Sukma; Buniarto, Edwin Agus; Saptaria, Lina (LPPM Universitas PGRI Sumatera Barat, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors that have a strategic role in driving national economic growth. One of the areas that has positive dynamics in the MSME sector is Kediri City, where the area has shown a significant increase in the number of MSMEs in recent years, based on this phenomenon, it is known that financial literacy has a significant influence in helping MSMEs manage their businesses sustainably through better investment decision making. investment decisions are also supported by the locus of control factor. Locus of control refers to an individual's belief about the extent to which an individual can control the results of their investment decisions. The data taken for this study were responses from participation, the responses were taken using a questionnaire method with a random sampling technique. The target in this study were MSME actors registered with the Indonesian Chamber of Commerce and Industry (KADIN) Kediri. The data collection method was a questionnaire, and the data analysis method was a Structural Equation Model (SEM) based on Partial Least Squares (PLS). The results of this study show a significant influence between risk perception on investment decisions, no significant influence between locus of control on investment decisions, no significant influence between risk perception on investment decisions with financial literacy as a moderating variable, no significant influence between locus of control on investment decisions with financial literacy as a moderating variable